Distribution and potential eco-risk of chromium and nickel in sediments after impoundment of Three Gorges Reservoir, China. Issue 1 (2nd January 2017) - Wang, Xiaoxiao; Bing, Haijian; Wu, Yanhong; Zhou, Jun; Sun, Hongyang
ABSTRACT: The impoundment of the Three Gorges Reservoir (TGR) altered the hydrodynamic conditions and modulated the accumulation and behaviors of heavy metals in the sediments. In this study, the sediments from the riparian and submerged areas of the entire TGR mainstream were collected in 2014 to investigate the spatial distribution of chromium (Cr) and nickel (Ni), and to assess their contamination state and potential eco-risk to aquatic environment by multiple indices. Results showed that the concentrations of Cr and Ni in the sediments increased toward the dam. The concentrations of Cr were significantly higher in the riparian sediments than in the submerged sediments, whereas the Ni concentrations were comparable. The relatively high storages of Cr and Ni in the sediments existed near the dam. The physiochemical properties of sediments and local human activities controlled the spatial variations of Cr and Ni in the sediments. Currently, the TGR sediments are not heavily contaminated by Cr and Ni and show low eco-risk. Nevertheless, considering the decrease in sediment loads from the upper Yangtze River and the rapid urbanization in the TGR catchment, much more attentions should be paid to the geochemical behaviors and the eco-risk of Cr and Ni in the sediments.